2019
DOI: 10.2355/isijinternational.isijint-2018-428
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Driving Demonstration of Li<sub>4</sub>SiO<sub>4</sub>/CO<sub>2</sub>/Zeolite Thermochemical Energy Storage System for Efficient High-Temperature Heat Utilizations

Abstract: Thermochemical energy storage (TcES) system using lithium orthosilicate/carbon dioxide (Li 4 SiO 4 /CO 2) reaction was developed for recovery and utilization of high temperature thermal energy generated from high temperature industrial process. Li 4 SiO 4 /CO 2 TcES packed bed reactor (LPR) and zeolite packed bed reactor (ZPR) were developed as thermal energy storage and CO 2 reservoir. Both reactors, LPR and ZPR, were connected by flexible tube and thermal driving operation of TcES system was demonstrated. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Especially for its utilization as a high temperature TcES, reactivities of Li 4 SiO 4 under high concentrations of CO 2 needs be investigated. In our previous work, the reactivity enhancement of K 2 CO 3 was also con rmed with Li 4 SiO 4 pellets at 600-700°C (Kim et al, 2019a(Kim et al, , 2019b. However, the reactivities of Li 4 SiO 4 with di erent ratios of K 2 CO 3 additives had not been completed under high concentrations of CO 2 .…”
Section: Introductionmentioning
confidence: 90%
“…Especially for its utilization as a high temperature TcES, reactivities of Li 4 SiO 4 under high concentrations of CO 2 needs be investigated. In our previous work, the reactivity enhancement of K 2 CO 3 was also con rmed with Li 4 SiO 4 pellets at 600-700°C (Kim et al, 2019a(Kim et al, , 2019b. However, the reactivities of Li 4 SiO 4 with di erent ratios of K 2 CO 3 additives had not been completed under high concentrations of CO 2 .…”
Section: Introductionmentioning
confidence: 90%
“…The composites incorporate materials that form a matrix to contain the salt and enhance cycle stability, thermal conductivity, and promote the heat and mass transfer. For instance, common composites using lithium salts are; activated carbon (AC) mixed with expanded natural graphite treated with sulfuric acid (ENG-TSA) [69,70], expanded graphite (EG) [71][72][73], activated alumina (AA) [74], expanded vermiculite (EVM) [75], Wakkanai siliceous shale (WSS) [76], silica gel (SG) [77], vermiculite (VM) [78][79][80], silica-alumina (S-AA) [81], zeolite (13X-Z, NaY-Z, Z) [82][83][84][85], graphene oxide (GO) [86]. In this sense Yu et al [69,70] developed a new type of consolidated composite sorbent using activated carbon (AC) as the porous matrix to harbour the LiCl salt.…”
Section: Lithium In Tcs Sorptionmentioning
confidence: 99%
“…The results revealed that LiOH•H2O/13X-Z presented the lowest apparent activation energy (21.5 kJ/mol) and the highest heat storage density 1949 kJ/kg (3 times higher than the pure LiOH). In a different research, Kim et al [83], studied the reaction of Li4SiO4/CO2 for recovery and utilisation of the high-temperature produced from industrial processes. To do this, two reactors (Li4SiO4/CO2 packed bed reactor (LRP) and zeolite packed bed reactor (ZPR)) were developed as TES.…”
Section: Lithium In Tcs Sorptionmentioning
confidence: 99%
“…To establish a carbon cycle system, CO 2 is reduced with non-fossil primary energy, and carbon resources such as carbon monoxide (CO) are recycled and reused. It is necessary to establish a rational CO 2 resource recycling and energy reduction technologies such as CO 2 electroreduction, [7][8][9] recycling of plastic waste, 10,11) utilization of scrap metal, [12][13][14] and waste heat recovery 15,16) in this system. To establish the iACRES, we have been studying CO 2 reduction technology using solid oxide electrolysis cells (SOECs).…”
Section: Introductionmentioning
confidence: 99%